Molecular dynamics simulations provide atomistic insight into hydrogen exchange mass spectrometry experiments - Petruk, Ariel Alcides (2013)
It is now clear that proteins are flexible entities that in solution switch between conformations to achieve their function. Hydrogen/Deuterium Exchange Mass Spectrometry (HX/MS) is an invaluable tool to understand dynamic changes in proteins modulated by cofactor binding, post-transductional modifications, or protein-protein interactions. ERK2MAPK, a protein involved in highly conserved signal transduction pathways of paramount importance for normal cellular function, has been extensively studied by HX/MS. Experiments of the ERK2MAPK in the inactive and active states (in the presence or absence of bound ATP) have provided valuable information on the plasticity of the MAPK domain. However, interpretation of the HX/MS data is difficult, and changes are mostly explained in relation to available X-ray structures, precluding a complete atomic picture of protein dynamics. In the present work, we have used all atom Molecular Dynamics simulations (MD) to provide a theoretical framework for the interpretation of HX/MS data. Our results show that detailed analysis of protein-solvent interaction along the MD simulations allows (i) prediction of the number of protons exchanged for each peptide in the HX/MS experiments, (ii) rationalization of the experimentally observed changes in exchange rates in different protein conditions at the residue level, and (iii) that at least for ERK2MAPK, most of the functionally observed differences in protein dynamics are related to what can be considered the native state conformational ensemble. In summary, the combination of HX/MS experiments with all atom MD simulations emerges as a powerful approach to study protein native state dynamics with atomic resolution.